Pengaruh managerial ownership, institutional ownership dan rasio keuangan terhadap struktur modal pada sektor perdagangan jasa dan investasi - ERIKA JIMENA ARILYN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
The purpose of this research is to test and analyze empirically the influence of managerial ownership, institutional ownership, growth asset, return on asset, dividen payout ratio, size, fixed asset ratio and corporate tax rate toward debt to equity ratio. Sample of this research is trade service and investment sector companies that listed in Indonesia Stock Exchange for period 2002-2013. The purpose sampling is used as sampling technique, where 6 companies met the criteria and were analyzed using descriptive statistic and panel data regressions with fixed effect model to test the hypotesis. The result of this research shows that institutional ownership and fixed asset ratio does influence debt to equity ratio, while managerial ownership, asset growth, return on asset, dividend payout ratio, size and corporate tax rate do not influence debt to equity ratio.